Digital Financial Literacy Training for Student Koperasi: Creating a Financially Intelligent Young Generation - Hayati, Nur; Wardhana, M Adhitya (Universitas Muhammadiyah Surakarta, 2025)
Understanding and skills in digital-based financial literacy are essential, this requires the younger generation, especially students, to have these skills. However, based on the National Survey of Financial Literacy and Inclusion in 2022, it showed a low financial literacy index among the 18-25 age group of 39.94%, therefore targeted educational interventions are needed. Community service activities were carried out to improve the digital financial literacy of the management of the Semarang University Student Koperasi (KOPMA) through training and mentoring. The implementation method consists of four stages, namely socialization and pre-test, interactive training, technical assistance, and evaluation and post-test. The results of the activity showed a significant increase in participant understanding, with the average post-test score increasing from 48 to 82. In addition, 92% of participants stated that they were ready to implement a digital financial recording system in management of koperasi. This activity succeeded in equipping participants with skills in using the Google Sheet and BukuKas applications for recording transactions, preparing financial reports, and cooperative cash planning. This program has an impact that effective digital financial literacy training can strengthen the governance of student cooperatives and form a young generation that is financially intelligent and adaptive to technological developments.